2020
DOI: 10.7150/ijbs.37686
|View full text |Cite
|
Sign up to set email alerts
|

E2F8 regulates the proliferation and invasion through epithelial-mesenchymal transition in cervical cancer

Abstract: The transcription factor E2F is an important modulator of the cell cycle, and the unrestricted activation of E2F-dependent transcription is considered to be an important driver of tumor formation and progression. E2F8 is known to play an important role in embryonic development and cell cycle control by inhibiting E2F1. However, it is not yet known whether E2F8 is involved in the progression of cervical cancer. In this study, the functional consequences of E2F8 knockdown in vitro and in vivo were explored. To d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Similarly, to what we observed in Msi1 knockdown or KO cells [ 3 ], inhibition of E2F2 expression arrests cell division in the G1 phase [ 94 ]. E2F8 is still poorly characterized in the context of brain tumors but it has been implicated in the development of various cancer types including lung cancer, lymphoma, colon cancer, cholangiocarcinoma, prostate cancer, hepatocellular carcinoma and breast cancer [ 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ]. E2F8 high expression is strongly associated with a worse outcome of GBM patients and radio-resistance while E2F8 knockdown decreased proliferation and tumor growth and inhibited invasion, migration and the expression of genes implicated in metastasis [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, to what we observed in Msi1 knockdown or KO cells [ 3 ], inhibition of E2F2 expression arrests cell division in the G1 phase [ 94 ]. E2F8 is still poorly characterized in the context of brain tumors but it has been implicated in the development of various cancer types including lung cancer, lymphoma, colon cancer, cholangiocarcinoma, prostate cancer, hepatocellular carcinoma and breast cancer [ 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ]. E2F8 high expression is strongly associated with a worse outcome of GBM patients and radio-resistance while E2F8 knockdown decreased proliferation and tumor growth and inhibited invasion, migration and the expression of genes implicated in metastasis [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports showed that E2F1 promotes EMT by regulating ZEB2 in small lung cancer [19]. Our previous research showed that E2F8 was also involved in invasion and metastasis by EMT in cervical cancer [20]. These results showed that E2F8 is closely associated with EMT, but the detailed mechanism of EMT regulation by E2F8 in ovarian cancer is unknown.…”
Section: Introductionmentioning
confidence: 91%
“…We also found that upregulation of E2F1/2/7/8 is an independent prognostic factor for patient OS and that genetic alterations of E2Fs were associated with poor DFS in cervical cancer, indicating that dysregulation of E2F1/2/7/8 may be associated with progression of cervical cancer. Because an oncogenic role of E2F1 and E2F8 in cervical cancer has been reported [24,25], we knocked down E2F2 and E2F7 by shRNA in cells from the cervical cancer cell lines HeLa and C-33 A, and further investigated to assess the effect of E2F2 and E2F7 knockdown on cellular functions of HeLa and C-33 A cells. We discovered that E2F2 and E2F7 knockdown suppressed proliferation and migration abilities, promoted cell cycle arrest, and inhibited stemness of both HeLa and C-33 A cells in vitro, suggesting that E2F2 and E2F7 may function as oncogenes, leading to tumor progression or metastasis of HPV-positive and HPV-negative cervical cancer.…”
Section: Discussionmentioning
confidence: 99%